Concomitant synthesis of beta-endorphin and alpha-melanotropin from two forms of pro-opiomelanocortin in the rat pars intermedia. - Crine, P (1979)
In the pars intermedia of rat pituitary glands, two forms of a common precursor for corticotropin (ACTH) and beta-lipotropin with apparent molecular weights of 34,000 and 36,000 were resolved by sodium dodecyl sulfate/acrylamide gradient slab gel electrophoresis. High-performance liquid chromatographic analysis of [35S]methionine-labeled tryptic fragments of the two forms of the precursor revealed that both contained copies of ACTH-(1-8) and beta-lipotropin-(61-69) sequences. When biosynthetic studies were performed in the presence of tunicamycin, the 34,000- and 36,000-dalton forms were replaced by a peptide with an apparent molecular weight of 32,000. It was therefore concluded that the 34,000- and 36,000-dalton forms of the precursor represent two glycoprotein variants of similar polypeptides, differing in the number of asparagine-linked carbohydrate moieties. During pulse-chase incubations with [35S]methionine, the precursor forms were cleaved into two major groups of labeled products: (i) beta-endorphin and (ii) a mixture of ACTH fragments closely related to alpha-melanotropin. No ACTH-(1-39) was found at the end of a 2-hr chase period, suggesting that ACTH is not a significant hormone product of the rat pars intermedia.